Chemical Analysis, Distributed Modelling and Risk Indices. Three Fundamental Pillars in Risk Assessment - Emilio Benfenati; Daniel Genah; Roberto Verro; Paulo Mazzatorta (The Scientific World Journal)
The Risk Assessment (RA) of pollutants from contaminated sites and landfills is a major environmental issue in Europe, due to the large number of sites and to the importance of groundwater protection. The high number of contaminants and the lack of knowledge of their environmental properties and their ecotoxicological and toxicological characteristics complicate the problem. Furthermore, this information about the chemicals has to be combined with the data relative to the territory and to the targets. We will describe the problems relative to each topic involved in the process, and we will propose an integrated methodology for coping with these problems, using state-of-the-art approaches in each part of the protocol. This methodology has been applied in several real cases.